Large area of walled‐off pancreatic necrosis successfully treated by endoscopic necrosectomy using a grasping‐type scissors forceps. Issue 3 (7th June 2013) - Aso, Akira; Igarashi, Hisato; Matsui, Noriaki; Ihara, Eikichi; Takaoka, Takehiro; Osoegawa, Takashi; Niina, Yusuke; Oono, Takamasa; Akahoshi, Kazuya; Nakamura, Kazuhiko; Ito, Tetsuhide; Takayanagi, Ryoichi
Abstract : Endoscopic necrosectomy (EN) for walled‐off pancreatic necrosis (WOPN) is less invasive than surgical treatment and has become the first choice for pancreatic abscess. EN is usually carried out with several devices including snares, baskets, and grasping forceps. Occasionally, we have encountered cases in which EN has not been satisfactorily carried out, and there is pressure for further innovation in EN. Here, we describe a case of a large area of WOPN that was successfully treated by EN with endoscopic submucosal dissection and associated techniques, which facilitated removal of necrotic tissues. A 60‐year‐old man was referred to our hospital for WOPN as a complication of necrotizing pancreatitis. As a result of his complicating conditions including ischemic heart disease, uncontrollable arrhythmia, chronic renalfailure, and persistent pleural effusion, he was deemed a poor surgical candidate. Although EN with conventional devices was carried out for five sessions, we could not remove the dense and massive necrotic tissues. At the sixth EN session, the Clutch Cutter device (Fujifilm, Tokyo, Japan) was used to remove the necrotic tissues, without major complications. This is believed to be the first report of EN using the Clutch Cutter for successful treatment of WOPN.